FOREIGN LANGUAGE ANXIETY, ENGLISH LEARNING MOTIVATION AND ACHIEVEMENT OF AGRICULTURAL MANAGEMENT STUDENTS OF SAMARINDA STATE POLYTECHNIC OF AGRICULTURE - Budi Rachmadani; Dyah Sunggingwati; Iwan Setiawan (Fakultas Ilmu Budaya, Universitas Mulawarman, 2019)
Language anxiety and language motivation have been an important area for empirical research and theoretical work within the context of second and foreign language. Thus, exploring the relationship between language motivation and language anxiety and their combined effects on the EFL achievement will help language teachers and researchers to clarify the role of these two variables in language pedagogy. The present study aims at finding out the broad profiles of the students’ foreign language anxiety and learning motivation and the relationship between foreign language anxiety and learning motivation. The correlational study was used to find out the relationship between variables. The Foreign Language Classroom Anxiety Scale (FLCAS) and English Learning Motivation Scale (ELMS) were used to collect the required data. The students’ achievement was represented by using the mid-test score. The result indicated that the participants have high level of English achievement (62.26) despite their low English learning motivation (40.08) and medium level of foreign language anxiety (47.25). The Pearson Product Moment Correlation shows that results from the correlation-based analysis demonstrated significant relationships among all variables.